Represemtasi Komunikasi Politik dalam Film The Trial of Chicago 7 - Mohammad Fakhruddin Arrazi; M. E. Fuady (UNISBA Press, 2022)
Abstract. This research is entitled 'Representation of Political Communication in the Film 'The Trial Of Chicago 7'. To achieve the research objectives, the researcher uses an interpretive paradigm, with a qualitative approach and John Fiske's semiotic analysis based on the level of reality with the code of speech and appearance, the level of representation with the camera and dialogue, and the level of ideology. The results of the study show that there is a representation of political communication in the film 'The Trial Of Chicago 7' which is seen from the three levels proposed by John Fiske. At the level of reality, the representation of political communication is seen from the aspect of speech and appearance. At the level of representation, camera codes that describe political communication through camera and dialogue aspects. The ideological level that can be locked, the depiction of political communication and political communication behavior carried out by the actors in predetermined scenes so that the key ideologies are class ideology, materialism, individualism, and race. Abstrak. Penelitian ini berjudul ‘Representasi Komunikasi Politik dalam Film ‘The Trial Of Chicago 7’. Untuk mencapai tujuan penelitian, peneliti menggunakan paradigma interpretif, dengan pendekatan kualitatif dan analisis semiotika John Fiske berdasarkan level realitas dengan kode ucapan dan penampilan, level representasi dengan kode kamera dan dialog, dan level ideologi. Dari hasil penelitian menunjukan ada representasi komunikasi politik dalam film ‘The Trial Of Chicago 7’ yang dilihat dari tiga level yang dikemukakan John Fiske. Pada level realitas, representasi komunikasi politik dilihat dari aspek ucapan dan penampilan. Pada level representasi, kode kamera yang menggambarkan komunikasi politik tercermin melalui aspek kamera dan dialog. Level ideologi yang dapat disimpulkan, penggambaran komunikasi politik dan perilaku komunikasi poltik yang dilakukan oleh para pemeran dalam scene-scene yang sudah ditentukan peneliti sehingga ideologi yang disimpulkan adalah ideologi kelas, materialism, individualism dan ras.